Convening on the influenza human viral challenge model for universal influenza vaccines, Part 2: Methodologic considerations. Issue 35 (14th August 2019) - Innis, Bruce L.; Scorza, Francesco Berlanda; Blum, Jeremy S.; Jain, Varsha K.; Aguilar, Anastazia Older; Post, Diane J.; Roberts, Paul C.; Wairagkar, Niteen; White, Janet; Bresee, Joseph
Abstract: In response to global interest in the development of a universal influenza vaccine, the Bill & Melinda Gates Foundation, PATH, and the Global Funders Consortium for Universal Influenza Vaccine Development convened a meeting of experts (London, UK, May 2018) to assess the role of a standardized controlled human influenza virus infection model (CHIVIM) towards the development of novel influenza vaccine candidates. This report (in two parts) summarizes those discussions and offers consensus recommendations. Part 1 covers challenge virus selection, regulatory and ethical considerations, and issues concerning standardization, access, and capacity. This article (Part 2) summarizes the discussion and recommendations concerning CHIVIM methods. The panelists identified an overall need for increased standardization of CHIVIM trials, in order to produce comparable results that can support universal vaccine licensure. Areas of discussion included study participant selection and screening, route of exposure and dose, devices for administering challenge, rescue therapy, protection of participants and institutions, clinical outcome measures, and other considerations. The panelists agreed upon specific recommendations to improve the standardization and usefulness of the model for vaccine development. Experts agreed that a research network of institutions working with a standardized CHIVIM could contribute important data to support more rapid development and licensure of novel vaccines capable of providing long-lasting protection against seasonal and pandemic influenza strains.